Older Australians and the housing aspirations gap - James, Amity; Rowley, Steven; Stone, W.; Parkinson, S.; Spinney, A.; Reynolds, M. (2019)
This report examined the housing aspirations of older Australians, defined as households over the age of 55. The number of older Australians increased by almost 3 million between 2006 and 2016. The research collected data through a national Australian Housing Aspirations (AHA) survey, interviews and focus groups, supplemented with data from the Australian Bureau of Statistics (ABS). Older Australians aspire to live in a variety of different locations, with the most popular choices being the middle to outer suburbs of capital cities (around 35%) and small regional towns (around 20%). Generally, they would like to own a detached dwelling (69%) with three bedrooms (50%) although there is an appetite for two-bedroom apartments, particularly in the 75+ age group. Older Australians do not wish to be in the private rental market with 80 per cent demanding ownership. Aspirations are driven by a desire for long-term, stable housing. While the number of bedrooms, building quality and dwelling type are important, safety and security and having somewhere that feels like home are critical for older Australians. The short and longer-term housing aspirations gap (the difference between current and ideal housing) for later life Australians is not large with over 90 per cent of the 2,400 older Australians responding to the AHA survey stating their current housing meets their short-term housing aspirations, while 70 per cent reported current housing meets longer-term aspirations. There is unmet demand, or a housing aspiration gap, for dwellings in small regional towns, separate houses, two and three-bedroom dwellings and home ownership. The housing aspirations gap is larger for renters, private and social, than for home owners. Policy innovation could deliver the housing and housing assistance required to meet the diverse aspirations of later-life Australians through four key avenues: Housing assistance to develop alternative home ownership options to improve security of tenure and facilitate ageing in place. Continued reform of the private rental sector to deliver a long-term, secure housing option. Better matching of new housing supply to aspirations, especially in the private rental sector, to meet the demand for two and three-bedroom houses (including attached) located in high level amenity locations. Giving social housing tenants more agency and choice in the selection of their homes, including for those caring for grandchildren. A central housing information service providing information on how to plan as housing needs change in later life; dwelling development options, such as subdivision, to assist ageing in place and broader help on navigating different sectors of the housing market as household circumstances change.